2004
DOI: 10.1002/macp.200400202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Parameters on the Supramolecular Organization of Rigid‐Flexible Polymers

Abstract: Summary: Rigid‐flexible polyethers consisting of terphenyl and aliphatic segments of various lengths along their main chains and disubstituted by dendritic wedges of various generations (G0, G1, and G2) are examined in their bulk states. Characterization of phase transitions has been performed by means of differential scanning calorimetry (DSC) and was supported by structural information obtained from small‐angle light scattering (SALS) and polarized optical microscopy (POM) experiments. In order to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Besides the main melting transition at about 446 K, a weak endothermic peak is observed at w323 K during the second heating run. Comparing this behaviour with that of the respective diol with the three phenylene rings [34], an increase in the main transition temperature is observed that is expected by the increase in the conjugation length. Nevertheless, the first transition at 323 K, is in the same range supporting the notion that is mostly related to the dodecyloxy side-chains.…”
Section: Synthesis and Thermal Propertiesmentioning
confidence: 66%
“…Besides the main melting transition at about 446 K, a weak endothermic peak is observed at w323 K during the second heating run. Comparing this behaviour with that of the respective diol with the three phenylene rings [34], an increase in the main transition temperature is observed that is expected by the increase in the conjugation length. Nevertheless, the first transition at 323 K, is in the same range supporting the notion that is mostly related to the dodecyloxy side-chains.…”
Section: Synthesis and Thermal Propertiesmentioning
confidence: 66%
“…Structural Analysis. (PPV/PPE)s 1 and 2 were processed at different temperatures using a microextrusion process to prepare macroscopically oriented filaments, and temperature-dependent structural parameters were extracted from their wide-angle X-ray patterns recorded using a 2D detector. 24i,, In all cases, diffractions were seen in the low-angle equatorial region. These periodicities are presumed to result from nanoscale segregation between π-conjugated polymer backbones and aliphatic side chains that are immiscible with each other.…”
Section: Resultsmentioning
confidence: 99%
“…586 Here aliphatic-aromatic segregation induced a greater-degree of order as evidenced by DSC, Small-Angle Light Scattering (SALS), TOPM, and XRD. 587 Oriented fiber XRD exhibited 2D layering of dendronjacketed terphenyl units and supported a N structure (Figure 148a) that is converted to an S phase (Figure 148b) upon annealing.…”
Section: Main-chain Polyethers and Polyestersmentioning
confidence: 95%